LOCAL GENIUS DALAM REVOLUSI MENTAL BANGSA PASCA REFORMASI - Samsudin Samsudin (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2016)
The  phenomenon of the  nation  caused mental shift multi-factor;  globalization  and  modernization which  led  to social  change, are  already  being  felt since  the  post-reform government. To overcome this, the government announced a spectacular effort Mental Revolution. One possible solution is to create a revolutionary strategy  (education) with the  mental approach of local genius.  Local genius  was  born  as a product of noble culture and existence needs revitalization to rebuild the nation’s mental. This paper  offers 9 (nine) revolutionary strategy (education) nation through the mental approach of local genius